Factors affecting the nutritional status of toddlers between the ages of 12-59 months in the workplace of UPTD Puskemas Batu Kambing - Fernando, Fenny; Pebrina, Melia; Fransisca, Dewi (Journal of Health Science and Medical Therapy, 2024)
Nutritional problems in children at this time are still high. Malnutrition will have an impact on the development and growth of children. The purpose of this study is to find out the Factors Related to the Nutritional Status of Toddlers Aged 12 – 59 Months in the Working Area of the UPTD Batu Kambing Health Center in 2023. The type of research used is quantitative with a crosssectional research design. The population is all mothers who have toddlers aged 12-59 months totaling 610 with a sample of 86 people. The sampling technique is purposive sampling. This research has been carried out in March – April 2023 at the UPTD Batu Kambing Health Center. The data used were primary data and secondary data, namely by conducting interviews with respondents, univariate and bivariate data analysis using the Chi-Square test. The results of the study were less than half, namely 21 respondents (24.4%) who experienced malnutrition, 36 respondents (41.9%) who had a low level of knowledge, 28 respondents (32.6%) with poor parenting and 37 respondents (43.0%) who had a history of infectious diseases. The results of the statistical test showed that the relationship between knowledge and nutritional status was obtained with a value of p = 0.005 (p < 0.05), parenting style with nutritional status was obtained with a value of p = 0.003 (p < 0.05) and the relationship between history of infectious diseases and nutritional status was obtained with a value of p = 0.007 (p < 0.05).  It can be concluded that there is a relationship between the level of knowledge, parenting, eating and history of infectious diseases with the nutritional status of toddlers aged 12 – 59 months at the UPTD Batu Kambing Health Center in 2023. It is recommended to health workers to provide counseling on nutrition and the provision of PMT to undernourished children and to mothers to increase maternal knowledge about nutrition and improve maternal parenting by learning how to feed children.